Islamic banking opportunities in a non-Islamic economy: Customer perspectives of New Zealand / Rubaiyet H. Khan ... [et al.] - H. Khan, Rubaiyet; Subramaniam, Geetha; Ali, Ershad; Parvin, Saida (Universit Teknologi MARA Cawangan Selangor, 2018)
New Zealand as a representative of a non-Islamic economy holds some unique characteristics. It is small enough to test a new banking concept without many risks at the same time the results can be replicated effectively in larger economies like Australia, Canada, UK and USA. The current study uses four exploratory interviews and a robust literature review to propose frameworks for future studies in this area of knowledge. The results suggest opportunities of a market that can be a source of effective knowledge for successful market entries for Islamic banks around the world. Finding of this study may be of interest of future researchers in this area as well as managers and bankers looking for future markets of Islamic banks.